Mobile and wireless communications networks : (World Scientific, 2003)
The revised full papers presented were carefully reviewed and selected for inclusion in the volume. The book is divided in sections on indoor wireless networking, multiple access techniques for wireless ad-hoc networking, telephony over packet switched networks, IP networks versus conventional switched networks, mobility management and access techniques, and mobility support in IP.